Pembelajaran Menulis Akademik Berbasis PjBL dan Teknologi Digital Bermuatan Isu Lingkungan untuk Penguatan Literasi Ekologis Mahasiswa - Hera Septriana; Dimas Yusuf Afrizal; Ahmad Wahyudi (JURNAL SKRIPTA, 2026)
The growing global concern over environmental issues requires higher education institutions not only to develop students’ academic competencies but also to foster ecological literacy. However, academic writing instruction in universities often remains theoretical and insufficiently connected to real-world contexts. This study aims to integrate environmental issues as a strategy to strengthen students’ ecological literacy through academic writing instruction using a Project-Based Learning (PjBL) approach. The study employed a qualitative approach involving students from the Indonesian Language and Literature Education program at a private university in Central Java who were enrolled in an academic writing course. Data were collected through classroom observations, student response questionnaires, and interviews with lecturers and students. The findings reveal that integrating ecological literacy into academic writing through project-based activities enriches the learning context and encourages students to explore environmental issues as the basis for their academic writing. The learning model also increases student engagement in the learning process, strengthens critical thinking skills, and supports the production of more contextual and research-based academic texts. In addition, the integration of ecological themes contributes to enhancing students’ ecological awareness of environmental issues. Therefore, this approach has the potential to serve as an alternative pedagogical strategy for developing more contextual and sustainability-oriented academic writing instruction. Keywords: ecological literacy, writing strategy, project-based learning.